Gambaran Tingkat Pengetahuan Dan Perilaku Higiene Sanitasi Pengolah Makanan Di Rumah Sakit Orthopedi Prof. Dr. R. Soeharso Surakarta - Fajriyati, Chintya Yusrina; , Endang Nur W.,SST.,M.Si.,Med (2016)
Introduction: Hygiene and sanitation is critical factors which are important in determining the quality of the food. Food handlers is one of contributor food to contamination. There are three factors that have major role on the occurrence of food poisoning related to food handler, including knowledge, attitudes, and practices. Training program is important to improve knowledge of food handler. However the knowledge and skill to maintain food quality are not always significant with a good behavioral changes of food handler food. Objective: To describe level of knowledge and hygiene and sanitation behavior of food handlers at Orthopedi Hospital Surakarta. Research methods: This was a descriptive study. Population and sample in this research were food handlers at Nutrition Department Orthopedi Hospital Surakarta (7 persons). Data of food handlers were obtained through questionnaires, whereas data of food handlers behavior were obtained through observation and structured interview method. Results: A total of (100%) of food handlers had a good knowledge of hygiene and sanitation. Most of food handlers behavior (57,1%) were unfavorable whereas (42,8%) of those were good. Suggestion: The hospitals should improve food handlers behavior about hygiene and sanitation. Nutritional Department needs to conduct intensify training of hygiene and sanitation intensively for food handlers.